2018
DOI: 10.1097/md.0000000000010210
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1A1 gene polymorphisms and cervical cancer risk

Abstract: Objective:This meta-analysis aims to examine whether the MspI and Ile462Val polymorphisms of cytochrome P450 1A1 (CYP1A1) are associated with cervical cancer risk.Methods:Eligible case–control studies were identified dated until July 2017. Pooled odds ratios (ORs) were used to assess the strength of the association between the two variants and cervical cancer risk.Results:Thirteen studies were eligible (2148 cases and 2252 controls) concerning MspI polymorphism and 8 studies were eligible (1466 cases and 1690 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
0
11
2
Order By: Relevance
“…Our results show a lack of significant association between m1 and m2 polymorphisms and cervical cancer risk, which as in several others tudies-done among Japanese, Israeli Jewish, Polish, Chinese, and Indian populations (Sugawara et al, 2003;Gutman et al, 2009;Roszak et al, 2014;Tan et al, 2016). To contrast, significant associations between m1 and/or m2 polymorphism and increased cervical cancer risk have been documented in several populations (Tan et al, 2017;Juárez-Cedillo et al, 2007;Jain et al, 2017;Li et al, 2016;Wang et al, 2017;Ding et al, 2018), and a meta-analysis indicated that the m1 (CC) genotype was associated with an increased risk for cervical cancer among Asians and Mixed populations (Wu et al, 2013). It is thus premature to conclude the role of m1 and m2 polymorphisms in cervical cancer development.…”
Section: Discussioncontrasting
confidence: 54%
“…Our results show a lack of significant association between m1 and m2 polymorphisms and cervical cancer risk, which as in several others tudies-done among Japanese, Israeli Jewish, Polish, Chinese, and Indian populations (Sugawara et al, 2003;Gutman et al, 2009;Roszak et al, 2014;Tan et al, 2016). To contrast, significant associations between m1 and/or m2 polymorphism and increased cervical cancer risk have been documented in several populations (Tan et al, 2017;Juárez-Cedillo et al, 2007;Jain et al, 2017;Li et al, 2016;Wang et al, 2017;Ding et al, 2018), and a meta-analysis indicated that the m1 (CC) genotype was associated with an increased risk for cervical cancer among Asians and Mixed populations (Wu et al, 2013). It is thus premature to conclude the role of m1 and m2 polymorphisms in cervical cancer development.…”
Section: Discussioncontrasting
confidence: 54%
“…In recent studies, polymorphic variants of various human leukocyte antigen (HLA) molecules have been linked to the development of CC [55]. Through a meta-analysis of existing data on CC, a recent study demonstrated that MspI and Ile462Val polymorphisms in CYP1A1 gene are potential risk factors for CC development [56]. Another study suggested a potential association between MBL2 gene exon1 polymorphisms and an increased risk of CC development [57].…”
Section: Introductionmentioning
confidence: 99%
“…GNMT translocation into the nucleus supports pyrimidine and purine synthesis, and lessens uracil incorporation into DNA in cells with folate depletion [70,71] . Its loss impairs nucleotide biosynthesis [72] . GNMT suppressor activity also relates to the regulation of cytochrome P450-1A1 gene expression [71,72] .…”
Section: Gnmt and Liver Cancer Suppressionmentioning
confidence: 99%
“…Its loss impairs nucleotide biosynthesis [72] . GNMT suppressor activity also relates to the regulation of cytochrome P450-1A1 gene expression [71,72] . The polymorphism of this gene increases the susceptibility to breast [73] , cervical [73] , and lung [74] cancers.…”
Section: Gnmt and Liver Cancer Suppressionmentioning
confidence: 99%
See 1 more Smart Citation